ANALYSIS OF GENDER DISCRIMINATION IN THE MOVIE TENGGELAMNYA KAPAL VAN DER WIJCK IN SOCIOLOGY PERSPECTIVE - Maulida Usna Aulia (Jurnal Komunikasi dan Media, 2026)
This research aims to analyze gender discrimination in the film "Tenggelamnya Kapal Van Der Wijck" from the perspective of sociology and feminism studies. The movie, adapted from a novel by Buya Hamka, depicts a tragic love story in a social context full of patriarchal cultural values. Using a qualitative approach and content analysis method, this study identifies and explores the representation of gender discrimination in the film's narrative, characters and dialog. The results of the analysis show that the film displays various forms of gender discrimination, such as gender stereotypes, subordination of women, and social control over women. These findings are analyzed using the theory of radical feminism, which highlights the role of patriarchal structures and cultural norms in the oppression of women. This research concludes that "Tenggelamnya Kapal Van Der Wijck" not only reflects the social reality of its time, but also criticizes and raises awareness about the importance of gender equality. The results of this study are expected to contribute to the study of feminism in the media and increase understanding of the importance of fairer gender representation in the film industry.